Hysteroscopy: a boon in abnormal uterine bleeding - Kulkarni, Grishma; Shinde, Kunaal K.; Thosar, Mayur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Aim of the study was to analyze retrospectively the efficacy of hysteroscopy in the diagnosis of abnormal uterine bleeding (AUB). Methods: Eighty-six women in the reproductive and perimenopausal age group (20-50 years) visiting the gynaecology OPD from March 2018 to February 2019 with the complaints of abnormal uterine bleeding were enrolled in the study. All the patients who underwent hysteroscopic examination were subjected to endometrial curettage; which was sent for histopathological examination (HPE). The hysteroscopic findings were then corelated and compared with HPE. Results: Mean age of the patients was 37.2 years. Around 60.46% patients presented within six months of complaints. Clinically, 54.65% were diagnosed as menorrhagia, 37.2% as polymenorrhoea and 8.13% as intermenstrual bleeding. On hysteroscopy, 44.1% showed abnormal pathology. The positive findings including polyps (8.13%), calcification (3.48%), submucous myoma (12.79%), necrotic mass and forgotten IUCD (2.32%) and adhesions in one case. On the other hand, the findings of histopathology; 56 patients (65.11%) had normal / proliferative / atrophic endometrium, 17 (19.76%) had hyperplasia, 10 (11.62%) had polyps and 3 (3.48%) had calcified endometrium. There was no significant difference between two modalities for normal / proliferative / atrophic endometrium. The HPE diagnosed slightly higher patients of hyperplasia as compared to hysteroscopy. Hysteroscopy diagnosed a higher number of patients with submucous myoma and necrotic mass. Conclusions: Hysteroscopy provided additional visual information for some pathologies which otherwise would remain undiagnosed by HPE.